Rhizosphere Soil Fungal Communities of Aluminum-Tolerant and -Sensitive Soybean Genotypes Respond Differently to Aluminum Stress in an Acid Soil - Shi, Qihan; Liu, Yuantai; Shi, Aoqing; Cai, Zhandong; Nian, Hai; Hartmann, Martin; Lian, Tengxiang (Frontiers in Microbiology, 2020)
Different soybean genotypes can differ in their tolerance towards aluminum stress depending on their rhizosphere-inhabiting microorganisms. However, there is limited understanding of the response of fungal communities to different aluminum concentrations across different genotypes. Here, we used metabarcoding of fungal ribosomal markers to assess the effects of aluminum stress on the rhizosphere fungal community of aluminum-tolerant and aluminum-sensitive soybean genotypes. Shifts in fungal community structure were related to changes in plant biomass, fungal abundance and soil chemical properties. Aluminum stress increased the difference in fungal community structure between tolerant and sensitive genotypes. Penicillium, Cladosporium and Talaromyces increased with increasing aluminum concentration and were enriched under the aluminum-tolerant genotypes at the highest aluminum concentration. Moreover, complexity of the co-occurrence network increased under the tolerant genotypes at the highest aluminum concentration. Collectively, increasing aluminum concentrations magnified the differences in fungal community structure between the two studied tolerant and sensitive soybean genotypes. This study highlights the possibility to focus on rhizosphere fungal communities as potential breeding target to produce crops that are more tolerant towards heavy metal stress or toxicity in general.